SOME APPROACHES FOR MAPPING WIKIPEDIA INFOBOX PROPERTIES TO WIKIDATA - Tạ Hoàng Thắng (Tạp chí Khoa học Đại học Đà Lạt)
Wikidata is an open, online database which stores the common resources of other Wikimedia projects. Unifying Wikipedia infoboxes was described in Phase II of Wikidata plan which aims to augment auto-translation to Wikipedia infobox templates and deals with the diversity of Infobox data in all languages. In this paper, we offer some approaches to map Infobox properties to Wikidata for improving our enrichment model. Our results can be a valuable resource for Wikidata to alignInfobox properties. We mainly focus on how to map Vietnamese and English properties to Wikidata.